2013
DOI: 10.1021/ic302784q
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Formation of a Pentanuclear Ni4Cu Heterometallic Complex Exhibiting a Vertex-Sharing Defective Double-Cubane Core and Diphenoxo- and Phenoxo/Azide Bridging Groups: A Magnetostructural and DFT Theoretical Study

Abstract: Sequential reaction of a N5O3 octadentate tripodal ligand with Ni(2+) and subsequently with Cu(2+) and azide ligand afforded the first example of a heterobridged (phenoxo/μ(1,1)-azido) pentanuclear heterometallic (Ni4Cu) compound, which exhibits a centrosymmetric vertex-sharing defective double-cubane structure. The study of the magnetic properties reveals that the compound shows ferromagnetic interaction interactions, leading to an S = 9/2 spin ground state. Density functional theory calculations on the X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…But the electron delocalization also plays a major role as the C5 atom of the imidazole is connected to a C=N bond outside the ring. Generally cobaltnitrogen bond lengths in low spin cobalt(II) complexes with Schiff-bases are in the range [42,43] of 1.85-1.99 Å, in the presented study such bond lengths are observed in the range of 1.88 Å to 1.96 Å, which supports the structure and oxidation state of the cobalt(II) complex. Complex formations with different metal salts by H2imida are reflected in the corresponding changes in UV spectra of ligand on addition of respective metal ions.…”
Section: Resultssupporting
confidence: 81%
“…But the electron delocalization also plays a major role as the C5 atom of the imidazole is connected to a C=N bond outside the ring. Generally cobaltnitrogen bond lengths in low spin cobalt(II) complexes with Schiff-bases are in the range [42,43] of 1.85-1.99 Å, in the presented study such bond lengths are observed in the range of 1.88 Å to 1.96 Å, which supports the structure and oxidation state of the cobalt(II) complex. Complex formations with different metal salts by H2imida are reflected in the corresponding changes in UV spectra of ligand on addition of respective metal ions.…”
Section: Resultssupporting
confidence: 81%
“…The phenoxo bridge is an excellent linking group to construct complexes with short metal–metal distances. The phenoxo-bridged complexes have attracted extensive attention for their optical, catalytic, biomimetic, redox, and magnetic properties. Particular interest has been focused on the relationship of the structure and the magnetic property because the complexes with various phenoxides exhibit different magnetic behavior. Previous research has shown that the exchange coupling constant between metal centers can be affected by several structural parameters, such as the distance between the adjacent metal ions (M), the magnitude of the M–O phenoxo –M angle and the out-of-plane shift of the phenyl ring, the substituents on the phenyl ring, and so on. …”
Section: Introductionmentioning
confidence: 99%
“…A class of quinoline based compounds has been explored and found to have the ability to inhibit platelet-activating factor (PAF) synthesis which also contributes to antiinflammatory properties [49]. The role of copper in the pathology of inflammation emphasizes a lot of evidence [50]. The thorough investigation of copper complexes with different ligands together with antiinflammatory drugs and of the copper containing enzyme super oxide dismutase (SOD) brought to light the various therapeutic value of copper which is concluded to be an exogenous anti-inflammatory agent.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%